PENGARUH PENAMBAHAN TULANGAN BAJA HALUS (BENDRAT) TERHADAP KUAT TEKAN, POLA RETAK, DAN KUAT LENTUR BETON SERAT - Asmawi, Bazar; Fuad, Indra Syahrul; Wijaya, Muhammad Meidy; Aminuddin, Kiagus Muhammad (Universitas IBA Palembang, 2025)
In Indonesia, infrastructure development such as bridges and buildings is rapidly advancing, with concrete serving as the primary material due to its compressive strength. However, concrete is susceptible to cracking caused by stresses and temperature variations, which can compromise the strength and safety of structures. These cracks can appear both before and after construction completion and are influenced by environmental factors as well as the inherent properties of the concrete itself. To address these weaknesses, various studies have shown that adding fibers, particularly steel wire fibers with high tensile strength, can help inhibit crack propagation. Therefore, research was conducted on the use of steel wire fibers with a content of 0.5–1.5% to investigate their effects on the mechanical strength and crack patterns of concrete with a compressive strength of 25 MPa. The compressive strength tests indicated that all samples experienced strength increases over time, with the addition of 1% and 1.5% steel fibers providing the most significant and stable improvements, accelerating hardening and enhancing the load-bearing capacity of the concrete. Crack patterns varied based on age and fiber concentration, with parallel crack patterns being more dominant at higher fiber contents, while cone-shaped and shear cracks were more common in concrete without fibers or with lower fiber contents. Keywords: Steel Wire Fiber; Concrete Compressive Strength; Concrete Crack Pattern; Concrete Flexural Strength.